An Analysis of EFL Students’ Difficulties in Writing At The Second Grade of SMAN 1 Wundulako - Bimas Reskiawan; Nasmah Riyani; Satriyani Satriyani (Fakultas Sastra - Universitas Muslim Indonesia, 2019)
This research was conducted to investigate the most difficult aspect faced by students in writing. The research question addressed in this research was: “what is the most difficult aspect faced by the students in writing?”.The design of this research was a case study. In conducting this research, the researcher took class XI IPA 1 of SMAN 1 Wundulako as a subject of the research with considerable that the class have the low est score in writing. The researcher used two kinds of data collection. They were questionnaire and interview. The sample of the research was class IX IPA 1 which consisted of 28 students. While in analyzing the data, the researcher analyzed the data of questionnaire by using the formula which proposed by Nazir and for the data of interview the researcher used technique of data analysis proposed Ngabut such as data reduction, data display and verifying and conclusion. In representing the analysis, it was found out that the students of SMAN 1 Wundulako especially in the second grade class XI IPA 1 got four difficulties in writing. They were content organization vocabulary and grammar. From four aspects of three components, the vocabulary mastery aspect was considered as the difficult aspects that faced by the students in writing. The third statement of vocabulary aspect in the questionnaire was a difficulties that often faced by the students. It was shown by the result of questionnaire and interview with the percentage 3,53 mean and writng test also to support its students lack vocabulary, its concluded students of SMAN 1 Wundulako difficulties in writing.